2022
DOI: 10.3389/fendo.2022.869921
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitation of Individuals With Diabetes Mellitus: Focus on Diabetic Myopathy

Abstract: Diabetes mellitus (DM) is a chronic metabolic disease characterized by high blood glucose levels, causing serious damage to the cardiovascular, respiratory, renal and other systems. The prevalence of type 2 diabetes mellitus (T2DM) was 6.28% in 2017, considering all age groups worldwide (prevalence rate of 6,059 cases per 100,000), and its global prevalence is projected to increase to 7,079 cases per 100,000 by 2030. Furthermore, these individuals are often affected by diabetic myopathy, which is the failure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 81 publications
0
6
0
Order By: Relevance
“…104 Additionally, physical training (exercise), based on the type, intensity, and duration of exercise, may improve mitochondrial function of muscle, attenuates oxidative stress, and increased the antioxidant capacity in muscle, and all may increase muscle mass and strength against the "fall" accident. 105 Furthermore, it is reported that T2DM patients may be at higher risk of poor cognitive perspective of osteoporosis because recent study showed that these T2DM patients expressed a low self-efficacy for both exercise and calcium intake experience. 106 Moreover, other components of healthy lifestyle may be also important for all patients with chronic illnesses, including pre-DM and DM patients to prevent the occurrence of osteoporosis and reduce fracture, such as adequate nutritional support, vitamin D supplementation, calcium replacement, and essential micronutrition supports.…”
Section: Prevention and Management Of Osteoporosis In T2dm: Modificat...mentioning
confidence: 99%
See 1 more Smart Citation
“…104 Additionally, physical training (exercise), based on the type, intensity, and duration of exercise, may improve mitochondrial function of muscle, attenuates oxidative stress, and increased the antioxidant capacity in muscle, and all may increase muscle mass and strength against the "fall" accident. 105 Furthermore, it is reported that T2DM patients may be at higher risk of poor cognitive perspective of osteoporosis because recent study showed that these T2DM patients expressed a low self-efficacy for both exercise and calcium intake experience. 106 Moreover, other components of healthy lifestyle may be also important for all patients with chronic illnesses, including pre-DM and DM patients to prevent the occurrence of osteoporosis and reduce fracture, such as adequate nutritional support, vitamin D supplementation, calcium replacement, and essential micronutrition supports.…”
Section: Prevention and Management Of Osteoporosis In T2dm: Modificat...mentioning
confidence: 99%
“…104 Additionally, physical training (exercise), based on the type, intensity, and duration of exercise, may improve mitochondrial function of muscle, attenuates oxidative stress, and increased the antioxidant capacity in muscle, and all may increase muscle mass and strength against the “fall” accident. 105…”
Section: Prevention and Management Of Osteoporosis In T2dm: Modificat...mentioning
confidence: 99%
“…The presence of diabetes and its related complications can accelerate the development of sarcopenia ( 2 ). For example, decreased mitochondrial function induces changes in muscle fiber composition and the transition from an oxidative to glycolytic fiber type, which leads to sarcopenia ( 3 ). Another mechanism that contributes to sarcopenia in diabetes is diabetic peripheral neuropathy (DPN) and reduction in motor neurons ( 4 ), which can cause muscle weakness, atrophy, and adipose tissue infiltration.…”
Section: Introductionmentioning
confidence: 99%
“…GDM was an independent risk factor for pregnant-specific urinary incontinence (PSUI), a urinary incontinence that starts during pregnancy [ 11 , 16 ]. This scenario of atrophy and the transition from oxidative to glycolytic fiber type [ 17 , 18 ] results in skeletal muscle changes, such as muscle weakness, a shift in fiber type composition, increased collagen deposition, and an elevated collagen type I/III ratio [ 13 , 14 , 19 ]. The latter characteristics mimic those found in the GDiM of PFM and RAM, and are considered a profile of skeletal muscle injury induced by GDM [ 14 , 20 , 21 ] associated with a decreased quality of life [ 22 ].…”
Section: Introductionmentioning
confidence: 99%